DOP56 Histologic disease activity correlates with endoscopic severity in patients with moderate to severe Crohn's Disease. (21st January 2022) - Reinisch, W; De Hertogh, G; Protic, M; Chan, L S; Magro, F; Pollack, P; Feagan, B G; Harpaz, N; Pai, R
Abstract: Background: The role of histopathology evaluation in Crohn's disease (CD) is not precisely defined. Due to the heterogeneity of phenotypes, the discontinuity of distribution, and the transmural nature of inflammation, the interpretation of histologic outcomes is complex. To analyze how histology relates to established outcomes in CD, we examined association between histologic and endoscopic disease activity measured by frequently used scores (simple endoscopic score for Crohn's disease [SES-CD], Robarts histopathology index [RHI], global histological activity score [GHAS]) and the association between histologic or endoscopic severity with inflammatory biomarkers in a cohort of patients with moderate-to-severe CD. Methods: Patients (N=191) who were enrolled in a phase 2 randomized clinical trial (NCT02891226) in patients with moderate-to-severe CD were assessed at baseline (BL) for endoscopic disease location and severity as measured by SES-CD. Biopsies were obtained during BL endoscopy from the edge of the ulcers and the most inflamed mucosa in terminal ileum and 4 colonic segments (ascending, transverse, descending, rectum; N=10/patient, 2 per location with the more severe score used), and scored by central readers blind to study treatment, timepoint, and response status using RHI and both modified and active GHAS (mGHAS: Q1, 3, 4, 5, 6; aGHAS: Q1, 4, 5, 6; see Fig. 1). Inflammatory biomarkers included fCLP and CRP; log-transformed values are used. Linear correlations between measures were determined using Pearson correlation coefficients (PCC) as exploratory analyses. Nominal p values are presented. Results: SES-CD correlated well with all 3 histologic measures examined (Fig. 1). While both fCLP and CRP correlated more closely with endoscopy than with histologic measures, fCLP had higher correlation with each histologic measure than CRP (Fig. 2). 64% of patients had the same disease location at BL when measured by endoscopy or histology. Patients with endoscopic colonic disease displayed histologic ileal involvement in up to 20% of cases, while 13% of patients with endoscopic ileal disease demonstrated histologic colonic involvement (Table 1). Conclusion: Although histologic disease activity in CD, as determined by 3 different measures, correlates well with endoscopic assessment of disease, histologic involvement provides complementary information on disease distribution and extension. Further analyses are required to understand the additive role of mucosal histology in CD.